Photobiomodulation therapy on puncture‐associated pain: A controlled randomized double‐blind clinical trial - Ferreira, Giovanna Fontgalland; Machado, Glaucia Gonçales Abud; Roncolato, Vinicius Leão; Ramalho, Karen Muller; Motta, Lara Jansiski; Bussadori, Sandra Kalil; Duran, Cinthya Cosme Gutierrez; Fernandes, Kristianne Porta Santos; Mesquita Ferrari, Raquel Agnelli; Chiniforush, Nasim; Horliana, Anna Carolina Ratto Tempestini (Photochemistry and photobiology, 2025)
Dental fear and phobia are prevalent worldwide, with local anesthesia being the most feared procedure. This study aimed to determine whether photobiomodulation therapy (PBMT), used as a pre‐anesthetic, could modulate puncture pain and enhance the effectiveness of local anesthesia. In this controlled, randomized, double‐blind study, 49 participants were divided into an experimental group (n = 24), which received infrared laser therapy (100 mW, at 808 nm, 8 J, 80 s at a single point) immediately before standard anesthesia; and control group (n = 25), which received the standard anesthetic technique and sham laser. Pain levels were measured using the visual analog scale, and anesthetic efficacy was assessed through electrical tests (latency), percentage of failures, and cartridge usage. Anxiety levels were evaluated using the Beck Anxiety Inventory. Cardiovascular parameters were evaluated through blood pressure, oxygen levels, and heart rate. This randomized, double‐blind study found no difference between groups in these experimental conditions. The bias toward a positive PBMT result was sufficiently removed. Autonomic responses of the PBMT group were maintained stable during the procedure. In a controlled, randomized, double‐blind study with 49 participants, photobiomodulation (PBM) as pre‐anesthetic therapy (808 nm, 100 mW, 8 J for 80 s) found no difference between groups in these experimental conditions. The bias toward a positive photobiomodulation therapy (PBMT) result was sufficiently removed. Autonomic responses of the PBMT group were maintained stable during the procedure.